2007
DOI: 10.1007/s00415-006-0495-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolites in definite amyotrophic lateral sclerosis

Abstract: Biomarkers beyond clinical assessment are needed in patients who suffer from amyotrophic lateral sclerosis (ALS). Here, single-voxel proton magnetic resonance spectroscopy ((1)H MRS) of the gray matter of the motor cortex and the white matter including the pyramidal tracts was used to investigate concentrations of N-acetylaspartate (NAA), creatine (Cr), choline (Cho), myoinositol, glutamate, and glutamine in patients with definite ALS in a longitudinal design (three measurements at study inclusion, after 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Whereas conventional brain MRI is unremarkable in ALS [4], 1 H-MRS has revealed various neurochemical abnormalities that may indicate underlying disease processes, including gliosis, glutamate excitotoxicity, and oxidative stress. 1 H-MRS studies over the years in humans with ALS have suggested abnormal levels of the following brain metabolites: N -acetylaspartate (NAA, marker of neuronal integrity) [57]; myo -inositol (mIns, putative marker of glial cells) [8,9]; glutamate (Glu, excitatory neurotransmitter) [10]; γ-aminobutyric acid (GABA, inhibitory neurotransmitter) [5]; and glutathione (GSH, thiol antioxidant) [11]. Nearly all of these studies included the primary motor cortex and its underlying white matter as a region of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas conventional brain MRI is unremarkable in ALS [4], 1 H-MRS has revealed various neurochemical abnormalities that may indicate underlying disease processes, including gliosis, glutamate excitotoxicity, and oxidative stress. 1 H-MRS studies over the years in humans with ALS have suggested abnormal levels of the following brain metabolites: N -acetylaspartate (NAA, marker of neuronal integrity) [57]; myo -inositol (mIns, putative marker of glial cells) [8,9]; glutamate (Glu, excitatory neurotransmitter) [10]; γ-aminobutyric acid (GABA, inhibitory neurotransmitter) [5]; and glutathione (GSH, thiol antioxidant) [11]. Nearly all of these studies included the primary motor cortex and its underlying white matter as a region of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies have shown a decrease in the NAA peak in the precentral cortex (with no differences for other metabolites) [96], a decrease in the NAA/Cho peak and an increase in the Cho/Cr peak [91]. …”
Section: Resultsmentioning
confidence: 99%
“…MRI can also demonstrate subtle changes in ALS patients such as T2 hypointensity in the precentral gyrus (52) and T2 hyperintensity in the corticospinal tract (53,54). However, these findings are nonspecific and lack diagnostic validity (5558).…”
Section: Discussionmentioning
confidence: 99%